La danse du wititi - Maria José Freire (Ateliers d'Anthropologie)
This article presents a first analysis of the wititi, a dance performed during patronal festivals in the Colca Valley (Arequipa, Peru). The hypothesis put forward is that this dance renders intergesturality processes visible. It encompasses and brings into dialogue different corporealities generated through processes of intensification of the social relations of this region. This study analyses the series of gesturalities that make up this dance, as well as their variations, while linking the values expressed by these dancing bodies to other elements of the performative group, such as garments and their embroidery. The bent body-straight body relationship—which is presented as one of the main local differentiations in the performance of the dance—shows how urban gesturalities contribute to giving a new meaning to a fundamental trope of the Andean social organisation: relations between the upper and lower valley.